CD151 Regulates T-Cell Migration in Health and Inflammatory Bowel Disease. Issue 2 (4th November 2015) - Zelman-Toister, Einat; Bakos, Eszter; Cohen, Sivan; Zigmond, Ehud; Shezen, Elias; Grabovsky, Valentin; Sagiv, Adi; Hart, Gili; Kaushansky, Nathali; Ben-Nun, Avi; Maharshak, Nitsan; Sonnenberg, Arnoud; et al.
Abstract: The continuous recirculation of mature lymphocytes and their entry into the peripheral lymph nodes are crucial for the development of an immune response to foreign antigens. Occasionally, the entry and the subsequent response of T lymphocytes in these sites lead to severe inflammation and pathological conditions. Here, we characterized the tetraspanin molecule, CD151, as a regulator of T cell motility in health and in models of inflammatory bowel disease. CD151 formed a cell surface complex with VLA-4 and LFA-1 integrins, and its activation led to enhanced migration of T cells. Picomolar levels of CCL2 that were previously shown to inhibit T-cell migration to lymph nodes suppressed CD151 expression and dissociated CD151-integrin complexes in T lymphocytes, resulting in attenuated migration toward T-cell attractant chemokines. To directly inhibit CD151 function, a truncated CD151 peptide fragment mimicking of the CD151 extracellular loop was designed. CD151 extracellular loop inhibited T-cell migration in vitro and in vivo and attenuated the development of dextrane sulfate sodium-induced colitis. Thus, CD151 is a key orchestrator of T cell motility; interference with its proper function results in attenuated progression of inflammatory bowel disease.